Global research trends on melasma: a bibliometric and visualized study from 2014 to 2023 - Wang, Li-Jun; Pang, Yao-Bin; Li, Wen-Quan; He, Qing-Ying; Zhang, Xue-Er; Liu, E.; Guo, Jing (Frontiers in Pharmacology, 2024)
Melasma, a prevalent pigmentary disorder, is characterized by its complex etiology, propensity for recurrence, and resistance to treatment. However, there is currently no research on melasma through bibliometrics and visualisation. This study analyses the hotspots and trends in the field based on 2709 publications from the Web of Science Core Collection (WOSCC). We carried out bibliometric analyses using Citespace software for different countries/regions, institutions, authors, and keywords. References were also analysed using VoSviewer. The results indicate that overall, there has been an increase in publications related to melasma since 2014. According to the analysis of the collaborative network diagram, the United States, Egyptian Knowledge Bank, and Benjakul Soottawat are the most contributing countries, institutions, and authors, respectively. Reference and keyword analyses have identified the pathogenesis and treatment of melasma as a prevalent topic in recent years. And how to find new treatment options and more effective therapeutic drugs is a future research trend. This is the first bibliometric and visual analysis of melasma-related literature to explore research hotspots and trends.